Comparison between active drag values estimated using both the velocity perturbation method and the A.I.S. assisted towing method - Mason, B.; Kolmogorov, S.; Wilson, B.; Toussaint, H.; Sinclair, P.; Schreven, S.; Sacilotto, G.; Dominguez, R.; Hazrati, P. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
An accurate measure of active drag and propulsion in swimming provides possibly the best quantitative measure of a swimmer`s technique. Presently the MAD, the VPM and the ATM are commonly used in an attempt to accurately obtain active drag values as an assessment of swimmer technique. The ATM system is relatively new compared to both the MAD and VPM systems. The ATM has been developed on similar grounds to that of the VPM with the exception that it uses assisted towing as well as resisted swims. Similar conditions for testing in both the VPM and ATM are required. A major difference between both is that the ATM produces intra stroke active drag and propulsion profiles rather than only a mean measure of active drag. This research tested swimmers using both ATM and VPM to compare the mean active drag values at maximum swim velocity.